Why do consumers buy paper bags? The Impact of Habit, Consumer Awareness and Sustainability as Drivers of Environmentally Responsible Consumer Behavior - Ardhiyansyah, Andri; Iskandar, Yusuf (The Es Economics and Entrepreneurship, 2023)
This study investigates the drivers of environmentally responsible consumer behavior among Indonesian consumers, focusing on the impact of habit, consumer awareness, and sustainability. A sample of 252 participants were surveyed to examine the relationship between sustainability values, consumer vulnerability awareness, community consumer instrumentality awareness, personal consumer instrumentality awareness, habits, and responsible consumer behavior. This study used Structural Equation Modeling (SEM) with Smart-PLS 4 to analyze the data. The results showed a significant positive relationship between sustainability values, dimensions of consciousness, habits, and responsible consumer behavior. The findings emphasize the critical role of high awareness, personal agency, and habitual behavior in promoting green choices. These insights provide valuable guidance for businesses, policymakers, and environmental advocates who want to encourage positive environmental change through consumer behavior.